SOLIDWORKS SIMULATIONEXPRESS ANALYSYS ON A DESIGNED PART - Cătălin IANCU (Fiabilitate şi Durabilitate)
In this paperwork are presented the SolidWorks analysis steps taken for to preliminary strength study of a designed part, using SimulationExpress module. There are presented the settings that have to be done for such analysis and the results shown by this software module. The MEF elements that are taken into account are specific to a static analysis completed with imposed safety factor distribution.